Fortalecimiento de los Sistemas Participativos de Garantía en la Comercialización de la Feria Agroecológica El Caserito Bolivarense en la ciudad de Guaranda al año 2018 - Jogacho Guano, Karla Maribel (2019)
The present research project is carried out due to the need to belong to a public entity of the Agroecological Fair "El Caserito Bolivarense", who wish to exercise their rights through a grouping or formation of a legal regulation, where the aforementioned persons are subject to the field of agriculture, formed by small farmers who support their economy in each of their homes. Currently the Fair has 24 members, integrated as the basis of each of their families, where they participate in the production and marketing of agroecological products for their better lifestyle and providing consumers to retake healthy foods through the statute establishes as main and legal founders all partners that integrate in the Association of Agricultural Producers "Caserito Bolivarense", where I start the research at the beginning of the year 2018 with the support of the authors, From point of view the whole association must relate to new strategies as the manual of functions applied with the Participatory Guarantee Systems that allows them to develop the functions in a hierarchical way in the administrative process with the small producers. It is important that this research project shows as a tool for the producers, achieving a participative process, integral and social which will accedera a It is satisfactory. Keywords: Participatory Guarantee Systems, Marketing, Association, Statute, Legalization, Manual.